2014
DOI: 10.1038/cddis.2014.232
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma protein (RB) interacts with E2F3 to control terminal differentiation of Sertoli cells

Abstract: The retinoblastoma protein (RB) is essential for normal cell cycle control. RB function depends, at least in part, on interactions with the E2F family of DNA-binding transcription factors (E2Fs). To study the role of RB in the adult testis, a Sertoli cell (SC)-specific Rb knockout mouse line (SC-RbKO) was generated using the Cre/loxP recombination system. SC-RbKO mice exhibited an age-dependent testicular atrophy, impaired fertility, severe SC dysfunction, and spermatogenic defects. Removal of Rb in SC induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 43 publications
4
54
0
Order By: Relevance
“…In the mouse testis E2F2 and E2F3 have been shown to be partially expressed in the same germ‐cell types as E2F1 (El‐Darwish et al ., 2006; Rotgers et al ., 2014). To our surprise there were no other E2Fs among the differentially expressed genes in E2F1 −/− ‐testis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the mouse testis E2F2 and E2F3 have been shown to be partially expressed in the same germ‐cell types as E2F1 (El‐Darwish et al ., 2006; Rotgers et al ., 2014). To our surprise there were no other E2Fs among the differentially expressed genes in E2F1 −/− ‐testis.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence double labeling of apoptotic cells with Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) or proliferating cells with 5‐bromo‐2′‐deoxyuridine (BrdU) coupled to detection of specific cell types with marker antibodies were done as described previously (Rotgers et al ., 2014). Spermatogonia were detected using Magbee antibody (a kind gift from V. Thane) and Sertoli cells using Wilm's tumor 1 (WT1) antibody from P10 and P40 testes, n  = 4 per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With aging, the distur bances in the SC organization and in spermatogenesis as a whole in RBcKO mice became more severe, lead ing to male sterility. The results obtained by Nalam et al (2009) were largely confirmed in another essen tially similar study (Rotgers et al, 2014), which was also performed using a model of mice knockout for the RB gene in SCs (SCs RbKO). The analysis of prolifer ative activity showed that the number of BrdU posi tive SCs in 30 day old SCs RbKO mice significantly increased.…”
Section: Introductionmentioning
confidence: 55%
“…These authors also found that the testes of 10 and 12 week old mutant mice expressed cytokeratin 18, a marker of immature fetal SCs, and that the levels of RNA that are normally used as a tem plate for retinoblastoma protein synthesis were greatly reduced. In addition, it was shown (Nalam et al, 2009;Rotgers et al, 2014) that, in adult mice knock out for the RB gene, apoptotic signaling cascades were triggered in the SCs that resumed active proliferation. These conclusions were made by these authors on the basis of enhanced expression of 47 genes associated with apoptosis (upregulation), which was detected by the microarray technique, and the appearance of TUNEL positive apoptotic nuclei in the SC popula tion.…”
Section: Introductionmentioning
confidence: 99%